HodgeRank as a new tool to explore the structure of a social representation - Oliveira, Luna R. N.; Lunardi, José T.; Calçada, Marcos; Pereira, Ana L.; de Jesuz, Danilo A. F.; Costa, Cristina (Frontiers in Physics, 2024)
Social representation theory is a branch of social psychology that aims to identify the framework of concepts, ideas, opinions, beliefs, or feelings shared by the individuals within a social group, regarding a social object. Two main problems arise in this theory. The first concerns the identification of the content of the representation, which is the set of cognitive elements shared by the group; the second concerns its structure, which is the way these elements are organized and related among themselves. It is desirable that the methods to address these problems be simple, in regards to the feasibility of the data collection, and reliable, in the sense that they should provide a clear picture of the content and the structure of the representation.No single method proposed in the literature until now fully satisfies these features at the same time. Here we propose the use of HodgeRank, a global ranking method based on the Hodge combinatorial theory, as a new tool to explore the structure of a social representation. In this proposal, the input data is the same as those required for the hierarchical word associations, which is the main method in the field of social representations. However, the HodgeRank provides richer results when compared to the usual approach to analysing this kind of data, based on the Verg és' double-entry table. The main outcome of the HodgeRank is a graph, analogous to an electric circuit, from which some structural elements of the representation can already be identified. Moreover, the HodgeRank technique identifies the sources of inconsistencies between the global ranking and the aggregated answers within the social group. We interpret such inconsistencies in terms of the stability of the representation and use them to raise conjectures about the potential dynamics of the representation. We illustrate the application of this method in the study of a social representation of COVID-19 within a group of students and also within a group of faculty members from higher education institutions in Brazil.